2020
DOI: 10.1002/ldr.3617
|View full text |Cite
|
Sign up to set email alerts
|

Urban expansion or poor productivity: Explaining regional differences in cropland abandonment in China during the early 21st century

Abstract: Cropland abandonment has long been recognized as a marginalization process in rural regions but recently also as a precursor to urbanization in peri-urban regions. This study aimed to evaluate the relative importance of urbanization and poor productivity in cropland abandonment. A thorough investigation was conducted on 345 cities/ towns at the prefecture level or higher in China using 500-m annual maps for 2003-2016. Cropland abandonment was spatiotemporally coupled with the urbanization. At a national scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…For example, the out-migration of agricultural labor [55,56]. As a result of rural-to-urban population migration, the double-cropping system of cropland decreased along with cropland abandonment, especially in low-quality croplands in the hilly rural and mountainous regions [55,57]. It is difficult to implement mechanized operations in mountainous and hilly terrain [58,59].…”
Section: Analysis Of Driving Factors For Shifts Of the Nldcmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the out-migration of agricultural labor [55,56]. As a result of rural-to-urban population migration, the double-cropping system of cropland decreased along with cropland abandonment, especially in low-quality croplands in the hilly rural and mountainous regions [55,57]. It is difficult to implement mechanized operations in mountainous and hilly terrain [58,59].…”
Section: Analysis Of Driving Factors For Shifts Of the Nldcmentioning
confidence: 99%
“…A series of agricultural stimulation policies since the start of the 21st century have also helped drive the movement of NLDC, including the elimination of the agricultural tax, increased agricultural subsidies, and increased grain price [4,57]. Since 2002, China has carried out agricultural tax reform in Hebei, Shandong, Henan, and Hubei provinces, which to some extent increased farmers' production enthusiasm [60] and caused the NLDC to move slightly westward after 2005.…”
Section: Analysis Of Driving Factors For Shifts Of the Nldcmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in socioeconomic elements, such as urbanization and industrialization, are considered to be the main driving force behind abandoned cropland [14,49,50]. With the development of urbanization and industrialization, the surplus rural labor force is gradually transferred to non-agricultural industries [51].…”
Section: Introductionmentioning
confidence: 99%
“…The direct effects resulted from the urbanization process led to a large amount of land converted to construction land and the migration of a large number of rural population to cities [16]. Urbanization leads to the separation of labor and cultivated land, and the emergence of "concurrent farming" or "abandonment of agriculture", which leads to the abandonment of cultivated land [17][18][19]. Based on a sample survey, the researchers found that the rate of cultivated land abandonment in mountainous areas of China was 14.32% from 2014 to 2015, the abandonment rate was the highest in the mountainous areas along the Yangtze River Basin [20]; at the same time, some scholars used meta-analysis to reveal the spatial and temporal characteristics of cultivated land abandoned at the national scale in China, and found that the abandoned land was mainly concentrated in southern China [21].…”
Section: Introductionmentioning
confidence: 99%